A new species of the genus Sinohaplotropis Cao et Yin, 2008 (Orthoptera, Acridoidea, Pamphagidae) from Amur River, Russia - Yin, Hai-Xiang; Zhang, Da-Peng; Yin, Zhan (Zootaxa, 2020)
The genus Sinohaplotropis Cao et Yin, 2008 is a valid genus and not a synonym of Haplotropis Saussur, 1888. A new species Sinohaplotropis amurensis sp. nov. is described in this paper from Russia. The new species is similar to Sinohaplotropis erenchuanensis Cao et Yin, 2008, but differs from latter by subgenital plate of male triangular, with large bifurcate apex in dorsal view, pronotum longer reaching first abdominal tergite, top of Kraus` organ narrow and interspace of mesosternum straight in the middle. Type specimen is deposited in the Hebei University, Baoding, Hebei, China.